Maritime Slave Trading in Fourteenth-Century Famagusta - Usta, Ahmet (Brill, 2019)
The third city of Cyprus is called Famagusta, situate[d] on the seashore: here are the harbours of all this sea and realm and a concourse of merchants and pilgrims. It lies directly opposite to Armenia, Turkey and Acon. It is the richest of all cities, and her citizens are the richest of men.